Corpectomy in Destructive Thoracolumbar Spine Disease. Issue 7 (1st April 2015) - Archavlis, Eleftherios; Papadopoulos, Nikos; Ulrich, Peter
<x xml:space="preserve">Abstract</x> Study Design. Retrospective cohort study. Objective. To give some insight in balancing cost and effectiveness of 3 different techniques of corpectomy in destructive thoracolumbar spine disease. Summary of Background Data. Although there are several accepted methods of surgical treatment of single-level corpectomy in destructive metastatic thoracolumbar spine disease, the choice depends on the surgeon's preference. The techniques may vary in perioperative morbidity and short- and long-term outcome, but no study so far has analyzed their cost-effectiveness. Methods. Seventy-five consecutive patients, mean age of 57 years (range: 39–72 yr) with single-level destructive thoracolumbar lesion underwent surgical treatment with 3 different techniques in 2 centers from 2009 to 2013. The 3 groups were (1) mini open transpedicular corpectomy, (2) conventional open transpedicular corpectomy, and (3) the combined posterior-anterior approach. The data were collected prospectively according to our protocol and subsequently analyzed. The clinical outcome was assessed comparing visual analogue scale score of back pain and the short form 12 (SF-12) questionnaire both pre- and postoperatively. The cost analysis was done calculating the operative time, hospital stay, and the implant cost. Results. The mean follow-up period was 25 months (range: 24–30 mo). The clinical outcome in terms of visual analogue scale score of thoracolumbar pain and SF-12 physical and mental score improvement (P < 0.005) were comparable with all 3 techniques. The radiological outcome was comparable with current available data. As the intensive care unit stay (average: 7 d) and the hospital stay were longer (average: 15 d) with combined posterior-anterior approach, the total cost was maximum (average: [Euro sign]20, 952) with this group. Conclusion. Using the posterior approach only was the most cost-effective technique, but the mini open was comparable with the conventional open transpedicular approach. Level of Evidence: 3